ADDRESSING INTERNET ADDICTION AMONG ADOLESCENTS: THE ROLE OF ISLAMIC RELIGIOUS EDUCATION IN PREVENTION AND INTERVENTION - Makmun Syukron; Zainudin; Rohana (JURNAL PENELITIAN KEISLAMAN, 2026)
Bullying remains a significant challenge in educational institutions, including Islamic boarding schools (pesantren), where intensive social interactions among students may create opportunities for both positive relationships and bullying behavior. This study aims to analyze the forms of bullying, the factors contributing to its occurrence, and the strategies employed to prevent bullying at Al-Falah Pancordao Islamic Boarding School, Central Lombok. This research adopted a qualitative field-study approach. Data were collected through observations, in-depth interviews, and documentation, and were analyzed using the interactive model of Miles, Huberman, and Saldaña, which includes data condensation, data display, and conclusion drawing. The findings reveal that verbal bullying is the most dominant form of bullying, manifested through teasing, mocking, ridiculing peers during classroom presentations, and assigning derogatory nicknames. Physical bullying was also identified, although it was limited to minor physical actions such as pinching and ear-pulling, which were often perceived as jokes among students.